Urgensi penerapan maharah kitabah pada peserta didik pondok pesantren Al-Azhar Bi'ibadillah - Nilma Wahyuni Nasution (Yayasan Haiah Nusratul Islam, 2024)
In learning arabic, there are four skills that must be mastered, namely, Maharah Kalām, Mahārah Qira`ah, Mahārah Istima´ and Mahārah Kitābah. Of these four skills, the final process and stage to studied is writing skills. Writing skills are skills that require a thinking process so that the result can be expressed in written form. This research was motivated by the discopery of student who had low ability in writing hijaiyah letters, therefore the researcher carried out an analysis and described the urgency of implementing Mahārah kitabāh learning for Al-azhar Bi’ibadillah Islamic boarding school students with the aim of improving writing skills. In connectio with the title, namely “the urgency of applying the Mahārah kitābah to students at the Al-azhar Bi’ibadillah slamic Boarding school”. This research use qualitative methods with data collection that is appropiate to the material. This research is also an observation method, researcher make observations of the parties connerned. The results of the research show that it is important to apply writing skills at the Al-azhar Bi’badillah islamic boarding school.